Education Equality of Public Services for Poor Communities in Indonesia - Yuli Fitrianto; Adi Hendro Purnomo; Ratih Fenty A. Bintoro; Pebiansyah Hafsari; Noor Wahyuningsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
Indonesia's educational system has undergone a shift from centralization to decentralisation due to the government's proactive efforts.  Several programmes have been initiated to promote decentralisation, aiming to provide equal educational opportunities for all students and reduce disparities, especially for those who are disadvantaged. However, in reality some practices may not align with expectations This research aimed to impact the unequal access to education and public services for impoverished communities in Indonesia Employing a descriptive method with a qualitative approach, this study is based in 2 regencies and 2 cities in East Kalimantan province: Samarinda City, Bontang City, North Penajam Paser Regency, and East Kutai Regency. The research focuses solely on high school (SMA) and Vocational High School (SMK) students from disadvantaged backgrounds.  Based on the analysis of the 4 districts/cities included in the study, it is evident that both local and central governments have been actively involved in enhancing education services. This is achieved through initiatives like the 12-year compulsory education, BOS funds, regional BOS funds, Poor Student Assistance (BSM), the Kaltim Cemerlang Scholarship, and quota allocations for underprivileged students. The interviews showed that the program has been running well and there is no discrimination.  However, there are some obstacles, such as data inaccuracy, facilities and infrastructure.